Injectable hydroxyphenyl derivative of hyaluronic acid hydrogel modified with RGD as scaffold for spinal cord injury repair. Issue 4 (23rd January 2018) - Zaviskova, Kristyna; Tukmachev, Dmitry; Dubisova, Jana; Vackova, Irena; Hejcl, Ales; Bystronova, Julie; Pravda, Martin; Scigalkova, Ivana; Sulakova, Romana; Velebny, Vladimir; Wolfova, Lucie; Kubinova, Sarka
Abstract: Hydrogel scaffolds which bridge the lesion, together with stem cell therapy represent a promising approach for spinal cord injury (SCI) repair. In this study, a hydroxyphenyl derivative of hyaluronic acid (HA‐PH) was modified with the integrin‐binding peptide arginine‐glycine‐aspartic acid (RGD), and enzymatically crosslinked to obtain a soft injectable hydrogel. Moreover, addition of fibrinogen was used to enhance proliferation of human Wharton's jelly‐derived mesenchymal stem cells (hWJ‐MSCs) on HA‐PH‐RGD hydrogel. The neuroregenerative potential of HA‐PH‐RGD hydrogel was evaluated in vivo in acute and subacute models of SCI. Both HA‐PH‐RGD hydrogel injection and implantation into the acute spinal cord hemisection cavity resulted in the same axonal and blood vessel density in the lesion area after 2 and 8 weeks. HA‐PH‐RGD hydrogel alone or combined with fibrinogen (HA‐PH‐RGD/F) and seeded with hWJ‐MSCs was then injected into subacute SCI and evaluated after 8 weeks using behavioural, histological and gene expression analysis. A subacute injection of both HA‐PH‐RGD and HA‐PH‐RGD/F hydrogels similarly promoted axonal ingrowth into the lesion and this effect was further enhanced when the HA‐PH‐RGD/F was combined with hWJ‐MSCs. On the other hand, no effect was found on locomotor recovery or the blood vessel ingrowth and density of glial scar around the lesion. In conclusion, we have developed and characterized injectable HA‐PH‐RGD based hydrogel, which represents a suitable material for further combinatorial therapies in neural tissue engineering. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1129–1140, 2018.